Changes in insecticide resistance and host range performance of planthoppers artificially selected to feed on resistant rice - Horgan, Finbarr G.; Garcia, Charle Patrick F.; Haverkort, Fay; de Jong, Peter W.; Ferrater, Jedeliza B. (Elsevier, 2020)
Host plant resistance has received considerable attention for the management of insect herbivores on crop plants. However, resistance is threatened by the rapid adaptation of target herbivores towards virulence (the ability to survive, develop and damage a host with major resistance genes). This study examines the potential costs and benefits of adaptation for virulence in herbivores. We continuously reared planthoppers, Nilaparvata lugens, on two susceptible and three resistant rice, Oryza sativa, varieties for 20 + generations. We then assessed the performance of selected planthoppers across a range of rice lines with distinct resistance genes. We found that planthoppers with long-term exposure to resistant hosts (particularly IR62 with the Bph3(t) and BPH32 gene loci, and PTB33 with the Bph3(t), BPH32 and BPH26 gene loci) gained virulence against related varieties with the same and different resistance genes, but planthoppers adapted to the resistant host IR65482-4-136-2-2 (BPH10 locus) had reduced performance on phylogenetically distant plants with distinct resistant genes. In choice bioassays, avirulent planthoppers showed marked preferences for susceptible lines, whereas virulent planthoppers were less selective of varieties. We also examined whether virulence was associated with insecticide susceptibility. We tested susceptibility to three insecticides using a topical application method. Populations selectively reared on IR65482-4-136-2-2 had increased susceptibility to imidacloprid and fipronil, representing a possible trade-off with virulence. In contrast, a population with virulence to the highly resistant variety PTB33 was 4.88 × more resistant to imidacloprid and 3.18 × more resistant to BPMC compared to planthoppers of the same origin but reared on the susceptible variety IR22. Our results suggest complex relations between insecticide resistance and virulence that vary according to insecticidal toxins and resistance genes, and include potentially increased insecticide-susceptibility (a trade-off) as well as common detoxification mechanisms (a benefit)